Shape coexistence and octupole correlations in Se 72 - Mukherjee A.; Bhattacharya S.; Trivedi T.; Singh R.P.; Muralithar S.; Negi D.; Palit R.; Nag S.; Rajbanshi S.; Raju M.K.; Kumar S.; Choudhury D.; Kumar R.; Bhowmik R.K.; Pancholi S.C.; Jain A.K. (My University, 2025)
In the present paper, we report the results from the study of excited states in the Se72 nucleus using the Cr50(Si28, α2p)Se72 fusion evaporation reaction at a beam energy of 90 MeV. The deexciting γ rays were detected using the Indian National Gamma Array (INGA). A total of ten new γ-ray transitions have been identified using the γ-γ coincidence technique. The Kπ=02+ band based on an isomeric state has been extended up to a (10+) state at 5.473 MeV excitation energy, and four new interconnecting transitions have been placed between this band and yrast band. Further, the enhanced interconnecting E1 transitions between positive- and negative-parity bands suggest the existence of octupole correlations in this nucleus. The characteristics of the observed bands in the experiment have been interpreted in terms of the total Routhian surface (TRS) calculations. © 2022 American Physical Society.